2017
DOI: 10.3390/su9040555
|View full text |Cite
|
Sign up to set email alerts
|

Explore the Buffering Effects of Perceived Hidden Inflation on Survival of Mobile Phone Service Providers in Taiwan

Abstract: Abstract:The purpose of this study is to examine the moderating role of perceived hidden inflation on the relationships between service quality, brand trust and brand loyalty. All data collected from the target population are analyzed through two-step structural equation modeling (SEM) and moderated multiple regression (MMR) to examine the hypotheses. 1,050 questionnaires are randomly distributed at 21 telecommunication service stores in Taiwan. Findings indicated that service quality has no direct impact on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This is because they continue to make purchases from the brand, even as competitors enter the market or offer similar products or services at a lower price. Past studies [2,89,91] have also confirmed that brand trust has a positive impact on behavioral loyalty. Hence, we proposed the following hypothesis: H10: BT is significantly linked to BHL.…”
Section: Relationship Between Brand Trust and Brand Loyaltymentioning
confidence: 79%
See 4 more Smart Citations
“…This is because they continue to make purchases from the brand, even as competitors enter the market or offer similar products or services at a lower price. Past studies [2,89,91] have also confirmed that brand trust has a positive impact on behavioral loyalty. Hence, we proposed the following hypothesis: H10: BT is significantly linked to BHL.…”
Section: Relationship Between Brand Trust and Brand Loyaltymentioning
confidence: 79%
“…Consumers are more inclined to remain loyal to a brand that makes them feel good, and trust plays a critical role in evoking these positive emotions [ 76 ]. When consumers have faith in a brand, they feel less apprehensive about doing business with it, resulting in a greater likelihood of attitudinal loyalty since they are more comfortable and confident in making purchasing decisions [ 2 ]. Additionally, when consumers trust a brand, they often develop a sense of affiliation and belonging to that brand, resulting in a stronger emotional connection to the brand and increasing attitudinal loyalty.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations